KETERTINDASAN MELAYU DALAM CERPEN SUKU POMPONG KARYA FEDLI AZIS DAN CERPEN RUMAH DI UJUNG KAMPUNG KARYA HANG KAFRAWI - NFN Marlina (Balai Bahasa Provinsi Riau, 2015)
Reading short stories Suku Pompong (Pompong Tribe) and Rumah di Ujung Kampung (House at the End of the Village) is like reading a historical reality that is happening on the ground of Riau Malay. The exploitation of forest resources on a large scale in recent decades in Riau Province has changed the land use of the area of intact forest into plantation area. The exploitation process causes friction in the community. The friction is eventually lead to conflict between communities and plantation companies. Their struggle to resolve conflicts and maintain their ancestral land, the strength of the company that has the license to the land and sadness when the public finally has always been on the losing side. This study objected to describe the objective reality of the Malay community in terms of land conversion, the communal land into plantations and reality of imaginative literature contained in the short stories Suku Pompong dan Rumah di Ujung Kampung. This study applied the sociology of literature approach, while the sociological approach to literature is a literary approach that specializes in reviewing literature by considering the social aspects. Based on these approaches, it can be concluded that short stories Suku Pompong and Rumah di Ujung Jalan are short stories that raised the reality of the Malay community.